2013
DOI: 10.1177/2156587213505112
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Antimutagenic, and Antioxidant Activities of Methanolic Extract and Chalcone Dimers (Lophirones B and C) Derived From Lophira alata (Van Tiegh. Ex Keay) Stem Bark

Abstract: The cytotoxic, antimutagenic, and antioxidant activities of methanolic extract and lophirones B and C derived from Lophira alata stem bark were evaluated. The extract and lophirones B and C significantly (P < .05) reduced the viability of Ehrlich ascites carcinoma cells. There were concentration-dependent reduction in 4-nitro-o-aminophenylenediamine and benzo[a]pyrene-induced frame shift mutation as well as aflatoxin B1-induced base pair substitution by the extract and lophirones B and C. The extract and lophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Ex Keay stem bark. Lophirones B and C inhibit 4-nitro-o-phenylenediamine and benzo [a]pyrene-induced frame shift mutation in TA98 and AFB 1 -induced base pair substitution in TA100 (Ajiboye et al 2014a). It also inhibits proliferation of Ehrlich ascite carcinoma cell (Ajiboye et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ex Keay stem bark. Lophirones B and C inhibit 4-nitro-o-phenylenediamine and benzo [a]pyrene-induced frame shift mutation in TA98 and AFB 1 -induced base pair substitution in TA100 (Ajiboye et al 2014a). It also inhibits proliferation of Ehrlich ascite carcinoma cell (Ajiboye et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration (1 mg/mL) was chosen based on the previous report by Ajiboye et al (2014a), while the cell viability of AFB 1 (9 nM) was reported by Ribeiro et al (2010).…”
Section: In Vitro Experimental Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This biflavanoid has also been reported to exhibit potent cytotoxicity activity against melanoma (UACC62), renal (TK10) and breast (MCF10) cancer cell lines [19]. Recently, Ajiboye found that lophirone C has relatively high anticancer, antimutagenic, and antioxidant activities [20]. Thus, although our results with O. holtzii and its constituents provide some scientific rationale for the use of this ethno-medicinal plant by the communities of the coastal region of Kenya, it also suggests the need for extending the study to other Ochna species and other bioactivities.…”
Section: Biological Activitymentioning
confidence: 99%